2018
DOI: 10.1186/s12886-018-0851-x
|View full text |Cite
|
Sign up to set email alerts
|

Corneal densitometry in high myopia

Abstract: BackgroundTo investigate corneal densitometry values obtained using Scheimpflug tomography in normal and highly myopic (HM) eyes and to assess the differences in densitometry values between them.MethodsHighly myopic and normal corneas were examined using the Pentacam Scheimpflug imaging system. Corneal densitometry was automatically performed over a 12-mm diameter area, which was divided on the basis of annular concentric zones (0–2 mm, 2–6 mm, 6–10 mm, 10–12 mm, total diameter) and depth (anterior layer: inne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 24 publications
0
18
1
Order By: Relevance
“…We hypothesize that the surgical operation may slightly compromise the transparency of the peripheral cornea. Dong et al [30] investigated the differences in corneal densitometry between high myopic patients and normal individuals and found that densitometry values of the high myopic patients were significantly lower than those of the normal individuals. The authors hypothesize that the natural loss of endothelial cell density in a high myopic population might lead to a decrease in corneal densitometry.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesize that the surgical operation may slightly compromise the transparency of the peripheral cornea. Dong et al [30] investigated the differences in corneal densitometry between high myopic patients and normal individuals and found that densitometry values of the high myopic patients were significantly lower than those of the normal individuals. The authors hypothesize that the natural loss of endothelial cell density in a high myopic population might lead to a decrease in corneal densitometry.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with other studies, we found significant correlation between increasing age and corneal densitometry, particularly in the more peripheral cornea. There was no relationship between age and densitometry in the central 0–2 mm annulus [ 5 , 45 , 51 ]. The stronger relationship between age and changes to densitometry in the peripheral cornea is likely due to a higher prevalence of age-related corneal changes in this region.…”
Section: Discussionmentioning
confidence: 99%
“…Scheimpflug densitometry is an objective, non-invasive method of measuring corneal density and thickness, providing quantitative maps with excellent repeatability [ 5 , 44 , 45 , 46 , 47 , 48 ]. Scheimpflug devices also provide information on corneal curvature across the corneal surface.…”
Section: Introductionmentioning
confidence: 99%
“…The recent studies (since 2015), which have analyzed the mechanical corneal properties in relation with the cell density of the corneal endothelium, have been unable to show a statistically significant correlation [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%